Developing analysis and testing plug‐ins for modern IDEs: an experience report1. (3rd October 2012) - Zhao, Dan; Choudhary, Shauvik Roy; Orso, Alessandro; Bishop, Judith; Notkin, David
SUMMARY Plug‐ins have become an important part of today's Integrated Development Environments (IDEs). They are useful not only for extending the IDEs' functionality but also for customizing the IDEs for different types of projects. In this paper, we discuss some features that IDEs should provide to support the development of a specific kind of plug‐ins—plug‐ins that implement program analysis and software testing techniques. To guide the discussion, we first provide a survey of existing testing and analysis plug‐ins and, for each of these plug‐ins, discuss the details of the IDE support they use. We then present a case study based on our personal experience with building a regression‐testing plug‐in for two different IDEs. Finally, we use our findings to make a generalized discussion on the kind of capabilities a platform should provide to better support the development of program analysis and software testing plug‐ins.Copyright © 2012 John Wiley & Sons, Ltd.